External Debt Statistics : Guide for Compilers and Users. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This Guide provides clear, up-to-date guidance on the concepts, definitions, and classifications of the gross external debt of the public and private sectors, and on the sources, compilation techniques, and analytical uses of these data. The Guide supersedes the previous international guidance on external debt statistics available in External Debt: Definition, Statistical Coverage, and Methodology (known as the Gray Book), 1988. The Guides conceptual framework derives from the System of National Accounts 1993 and the fifth edition of the IMFs Balance of Payments Manual(1993). Preparation of the Guide was undertaken by an Inter-Agency Task Force on Finance Statistics, chaired by the IMF and involving representatives from the BIS, the Commonwealth Secretariat, the European Central Bank, Eurostat, the OECD, the Paris Club Secretariat, UNCTAD, and the World Bank.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet